FORUM PRIVILEGIATUM SEBAGAI WUJUD PERADILAN YANG ADIL BAGI MASYARAKAT - Sastra Panjaitan, Budi (Jurnal Media Hukum, 2018)
This paper aims to find out whether the privilegatum forum is needed or not to bring about a fair justice for the community. The state provides fair recognition, guarantee, protection and legal certainty for everyone without distinction of ethnicity, religion or position, including the poor who are unable to have access to justice properly, but in reality justice is not easily obtained, including those who are economically is under. Justice is illustrated more easily by those with special standing as state officials. In order to realize the balance of law and balance the sense of justice in the community, it is time for the forum privilegatum made a permanent choice for state officials who commit criminal acts. Through the privilegatum forum, the dismissal and punishment of state officials committing crimes is committed through special court mechanisms. This special tribunal is the first and final courts whose decisions are final and binding.